2020
DOI: 10.1155/2020/8076105
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Attenuate Diabetic Lung Fibrosis via Adjusting Sirt3-Mediated Stress Responses in Rats

Abstract: Diabetes affects a variety of organs such as the kidneys, eyes, and liver, and there is increasing evidence that the lung is also one of the target organs of diabetes and imbalance of Sirt3-mediated stress responses such as inflammation, oxidative stress, apoptosis, autophagy, and ER stress may contribute to diabetic lung fibrosis. Although previous studies have reported that mesenchymal stem cells (MSCs) have beneficial effects on various diabetic complications, the effect and mechanisms of MSCs on diabetes-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 87 publications
2
21
0
Order By: Relevance
“…Accumulating evidence has firmly implicated a key role for SIRT3 deficiency in the pathobiology of IPF as well as the bleomycin murine model of lung fibrosis, but the detailed molecular mechanisms involved are not fully understood, nor is it known whether augmenting SIRT3 in mice following exposure to asbestos is protective [32][33][34][35][36][37][38][39]. In this study we addressed these two important gaps in our understanding of the role of SIRT3 in modulating pulmonary fibrosis by showing that Sirt3 Tg mice are protected from asbestos-induced pulmonary fibrosis and that lung protection is associated with reduced levels of lung mtDNA damage and fibrogenic Mo-AM recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has firmly implicated a key role for SIRT3 deficiency in the pathobiology of IPF as well as the bleomycin murine model of lung fibrosis, but the detailed molecular mechanisms involved are not fully understood, nor is it known whether augmenting SIRT3 in mice following exposure to asbestos is protective [32][33][34][35][36][37][38][39]. In this study we addressed these two important gaps in our understanding of the role of SIRT3 in modulating pulmonary fibrosis by showing that Sirt3 Tg mice are protected from asbestos-induced pulmonary fibrosis and that lung protection is associated with reduced levels of lung mtDNA damage and fibrogenic Mo-AM recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Third, overexpression of SIRT3 using either genetic or pharmacologic approaches mitigates oxidant-induced fibroblast profibrotic signaling and AEC mtDNA damage and apoptosis in vitro as well as bleomycin-induced lung fibrosis in vivo [32][33][34][35]37,38] and promotes lung fibrosis resolution in aged mice [35]. Mesenchymal stem cells can diminish diabetic lung fibrosis by augmenting SIRT3 protein expression and SIRT3-mediated stress response [39]. Our group has established a causal role for the recruitment of pro-fibrotic monocyte-derived alveolar macrophages (Mo-AMs) in the development of both bleomycin-and asbestos-induced lung fibrosis, but the role of SIRT3 in modulating recruitment of Mo-AMs is unclear [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrated that loss of AIBP significantly reduced the expression levels of SIRT3 and SOD2 proteins in the inner retina including RGCs. Recent evidence indicates that the SIRT3-SOD2 pathway is linked to inflammation and oxidative stress [ 75 , 76 ]. In line with these and our findings, it is possible that mitochondrial AIBP may contribute to the stabilization of the SIRT3-SOD2 axis, rescuing RGC mitochondria from neuroinflammation and/or oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Acute lung injury is a common clinical syndrome in heavy patients, mainly manifested as destruction of alveolar capillary barrier function and interstitial edema ( Nugent et al, 2019 ). At present, it is believed that the pathogenesis of sepsis induced lung injury is mainly the inflammatory response, and the activation of inflammatory cells and the release of inflammatory factors induce the apoptosis and oxidative stress injury of alveolar epithelial cells, and eventually leads to alveolar epithelial dysfunction ( Chen et al, 2020 ). Therefore, fighting against inflammation, apoptosis, and oxidative stress is an important means to treat sepsis induced lung injury, which is of great significance for restoring homeostasis and improving organ failure.…”
Section: Discussionmentioning
confidence: 99%